Does female representation on corporate boards boost the strengthening of internal control in socially responsible firms? - Oleh Pasko; Zhang Yang; Viktoriia Tkachenko; Nelia Proskurina; Iryna Pushkar (Investment Management & Financial Innovations, 2022)
This study examines the relationship between corporate social responsibility and the effectiveness of internal control, while simultaneously examining board gender diversity to check whether female directors contribute to corporate transparency or not. The sample of the study comprises 15,231 firm-year observations of companies listed on the Shanghai and Shenzhen stock exchanges from 2013 to 2018. The raw data for variable calculation come from authoritative and reputable sources, such as China Stock Market and Accounting Research (CSMAR), DIB Internal Control database, and RKS CSR score. The empirical study shows that socially high-performing firms possess a more effective internal control mechanism. However, the paper failed to find a positive association of gender diversity on the board with internal control effectiveness, and failed to attest reinforcing effect of female directors on internal control in socially responsible firms. This study suggests that in China’s institutional environment, female directors are unlikely to contribute to increased corporate transparency. This study is useful for both regulators and company management to establish a master plan and tactics for board composition to improve corporate transparency, taking into account the effect of the investigated phenomena within the jurisdiction under study. AcknowledgmentThis paper is co-funded by the European Union through the European Education and Culture Executive Agency (EACEA) within the project “EMBRACING EU CORPORATE SOCIAL RESPONSIBILITY: CHALLENGES AND OPPORTUNITIES OF BUSINESS-SOCIETY BONDS TRANSFORMATION IN UKRAINE” 101094100 — EECORE — ERASMUS-JMO-2022-HEI-TCH-RSCH-UA-IBA / ERASMUS-JMO-2022-HEI-TCHRSCH https://eecore.snau.edu.ua/